2019
DOI: 10.1097/md.0000000000015134
|View full text |Cite
|
Sign up to set email alerts
|

A clinical research on the potential pathogenesis of somatic cancer related cerebral venous sinus thrombosis

Abstract: To investigate the pathogenesis of somatic solid cancer-related cerebral venous sinus thrombosis (CVST). A total of 174 patients with CVST were recruited from the hospital between January 2006 and December 2017 and divided into two groups: (1) somatic cancer-related CVST group, defined as active somatic solid cancer patients with acute CVST; (2) cancer group (CG), defined as active somatic solid cancer patients without CVST. The cancer group patients were age and gender-matched somatic cancer-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…No previous studies have reported a relationship between lymph node metastasis in tongue cancer and the PNR. Xian et al 19 studied 174 patients with solid carcinoma‐related cerebral venous sinus thrombosis and found that the higher PNR, the higher the probability of intracranial metastasis in these patients. This finding is similar to our finding that when PNR was >60.889, OTSCC patients were more prone to early‐stage lymph node metastasis, their innate immunity was weakened, their neutrophil count was decreased, and their PLT count was unchanged, resulting in an elevated PNR.…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies have reported a relationship between lymph node metastasis in tongue cancer and the PNR. Xian et al 19 studied 174 patients with solid carcinoma‐related cerebral venous sinus thrombosis and found that the higher PNR, the higher the probability of intracranial metastasis in these patients. This finding is similar to our finding that when PNR was >60.889, OTSCC patients were more prone to early‐stage lymph node metastasis, their innate immunity was weakened, their neutrophil count was decreased, and their PLT count was unchanged, resulting in an elevated PNR.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for CVST in the somatic cancer-related CVST group increased independently by 0.7% (odds ration [OR] 1.007; 95% confidence interval [CI] 1.000, 1.015; P = 0.047) with a 1 ng/ml increase in D-dimer levels and by 4.6% (OR 1.046; 95% CI 1.011, 1.083; P = 0.010) with a 1U/ml increased in carcinoembryonic antigen. 42 In the current case, the patient's D-dimer and CA125 levels were high. Therefore, for cancer patients, it is essential that coagulation indices are measured to prevent the occurrence of CVST.…”
Section: Discussionmentioning
confidence: 56%
“…But new-onset recurring headaches need a high index of suspicion for treatable conditions like CVST as we can improve outcomes in such patients. Our patient had a previous history of cancer, and about 7-10% of patients diagnosed with CVST have cancer (65). Even though it is unlikely that his treated cancer which is in remission caused CVST, it is important to note that cancer increases the risk of thrombosis (66).…”
Section: Discussionmentioning
confidence: 86%